URGENSI ILMU ASBAB AL-WURUD DALAM PENGEMBANGAN PEMAHAMAN HADIS - Qoidatul Marhumah (IAIN Kediri, 2018)
The optimalization of hadithâ€™ roles as guidance in life is not easy since hadith is born form the history in different context and reality. In fact, the reality is always developed and changed. This is always raising big question â€œcan hadith accommodate the contemporary problems?â€ To answer this question, the scholars (ulama) effort continuously to give guides in understanding hadith correctly to avoid misunderstanding. One of them is by studying asba>b al-wuru>d hadith. This article explains the significance of asba>b al-wuru>d that is called as the background of hadith rising, giving direction for us when the hadith is rising, why , to whom it is given, in what case, and how is the socio history of the hadith. Through this approach, it can be known the meaning of the hadith correctly and can be used correctly. Keywords; Hadith, asba>b al-wuru>d, contemporary problems